2018
DOI: 10.1111/vox.12656
|View full text |Cite
|
Sign up to set email alerts
|

Thrombin generation potential and clot‐forming capacity of thawed fresh‐frozen plasma, plasma frozen within 24 h and solvent/detergent‐treated plasma (octaplasLG®), during 5‐day storage at 1–6°C

Abstract: To enable rapid availability of plasma in emergency situations, the shelf-life of thawed fresh-frozen plasma (FFP) has been extended from 24 h to 5 days. The aim of this study was to evaluate the thrombin generation (TG) potential and clot-forming ability during 5 days of refrigerated storage of thawed FFP, plasma frozen within 24 h and solvent/detergent-treated plasma octaplasLG . During storage for 5 days, TG capacity decreased significantly over time, and rotational thromboelastometry showed significantly p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 9 publications
0
8
1
Order By: Relevance
“…This is different from another study which did not report significant differences between the D4 and D0 ETP values . On the other hand, a more recent published study (involving FP24 instead of RTFP24) showed similar decline in all CAT parameters after 120 h post‐thaw .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This is different from another study which did not report significant differences between the D4 and D0 ETP values . On the other hand, a more recent published study (involving FP24 instead of RTFP24) showed similar decline in all CAT parameters after 120 h post‐thaw .…”
Section: Discussioncontrasting
confidence: 99%
“…While there is published literature establishing the equivalence between FFP and RTFP24 upon thawing, few have compared global assays of haemostasis like thrombin generation. There were also less published literature reports on extended storage of thawed RTFP24 as most were conducted on thawed FFP or FP24 , and most did not directly compare RTFP24 with FFP beyond 24 h post‐thaw.…”
Section: Introductionmentioning
confidence: 99%
“…Several in vitro studies reported that factor activity in S/D plasma thawed for more than 24 hours remains high enough for clinical use. 5,32,33 Although labile factors, such as Factor V, VII and VIII can decline during 5-day storage, levels remained comparable to those in TP. The present retrospective study provides preliminary clinical evidence that T-S/D can correct coagulopathies as well as TP and the use of T-S/D does not have an adverse effect on in-hospital mortality, readmission rates, LOS and in-hospital DVT.…”
Section: Discussionmentioning
confidence: 96%
“…These in vitro studies evaluated factor antigen levels and activity of the plasma units, finding T-S/D equivalent to TP. [32][33][34][35] In 2016, our institution extended the expiration date of S/D plasma from 24 hours to 5 days post-thaw and implemented T-S/D as a routine plasma product. The aim of this retrospective pilot study was to determine whether T-S/D is clinically equivalent to TP.…”
Section: Introductionmentioning
confidence: 99%
“… 148 Coagulation factor levels after 5 days of storage of thawed solvent-/detergent-treated pooled plasma are essentially the same as found in thawed single-donor plasma. 149 In the US, the FDA currently approves use of octaplast for acquired factor-deficiency coagulopathies due to liver disease or that develop during the course of cardiovascular surgical procedures and liver transplantation. 150…”
Section: Damage Control Resuscitationmentioning
confidence: 99%